DINÁMICA DEL AGUA DEL SUELO EN DEHESA BAJO DIFERENTES CUBIERTAS VEGETALES. RESULTADOS PRELIMINARES. - Lozano Parra, F. J.; Schnabel, S.; Ceballos Barbancho, A. (Estudios en la Zona no Saturada del Suelo, 2008)
Dehesa ecosystems, characterized by a disperse tree cover of the genus Quercus, constitute a resource of great importance in large parts of SW Iberian Peninsula. Generally these areas are conditioned by their environmental limits such as shallow soils, seasonal and intraannual rainfall variability, which determine the availability of water for plants. The main objective of the present work is the study of soil water dynamics in dehesas, explaining the effect of different vegetation covers and soil characteristics. Soil moisture is determined in 15 stations, distributed in three farms in Extremadura, each of them composed of sensors located at various depths which register soil moisture continuously with a time resolution of 30 minutes. The stations are distributed in open areas (pasture), below the canopy of the shrub Retama sphaerocarpa and below the canopy of Quercus rotundifolia. First results indicate complex soil water dynamics with contrasting situations at sites with the same vegetation cover, and showing that various situations may be produced in the same station during a hydrological year. Furthermore, the largest variations are observed in the upper soil layer, being soil moisture variations lowest at greater depth, independently of the vegetation cover.
Keywords: bajo copa; Dehesa; humedad del suelo; pastizal; Quercus rotundifolia (voyant); retama sphaerocarpa

Estudio de la variabilidad temporal y espacial de la pérdida de suelo en la dehesa (Extremadura, SO España) mediante lluvia simulada - Ceballos Barbancho, A.; Shanabel, S.; Cerdà, A. (Geographicalia, 2002)
The inain objective of this paper is to study the influence of the seasonal variability of tlze antecedent conditions in soil losses in a dehesa ecosystem, as well as an approach to its spatial variability. The experimental layout includes forty rainfall simulation experiments carried out in two different situa- tions: first on dry conditions, with degraded vegetation, and, second on wet con- ditions, with an important vegetation cover. The results indicate that the highest sediiilent concentrations are located in situations with bare soils, due to the effect of the drought and the soil remo- ved by grazing animals. The control of the process depends more to tlie sediment available on the soil surface than to the runoff transport capacity. From an spatial point of view, it liighlights the contrast between tlie low los- ses registered in the valley bottoms and the highest values measured in tlie areas more frequented by the livestock, where the degradation of the vege- tation cover and the removal of tlie soil material are continuous. Finally, although the rate of soil loss in the dehesa is low, it is important froin a qua- litative point of view because it affects to the inost fertile horizon in the soil profile
Keywords: Dehesa; rainfall simulation; runoff; Season; sediment concentration; soil loss